2019
DOI: 10.1186/s13049-019-0609-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of the serum lactate level, the SOFA score and the qSOFA score for mortality among adults with Sepsis

Abstract: Background Sepsis is a common critical condition caused by the body’s overwhelming response to certain infective agents. Many biomarkers, including the serum lactate level, have been used for sepsis diagnosis and guiding treatment. Recently, the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) recommended the Sequential Organ Failure Assessment (SOFA) and the quick SOFA (qSOFA) rather than lactate for screening sepsis and assess prognosis. Here, we aim to explore an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(196 citation statements)
references
References 37 publications
(50 reference statements)
7
169
4
4
Order By: Relevance
“…Accumulation of lactate in the tissue microenvironment is also a feature of sepsis ( 10 ). It has been indicated that the physiological lactate concentration in blood or healthy tissues is approximately 1.5 – 3 mM ( 39 ), while the blood lactate levels in septic patients can reach over 20 mM ( 40 ). Remarkably, lactate levels can rise to 40 mM at the inflamed tissues ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of lactate in the tissue microenvironment is also a feature of sepsis ( 10 ). It has been indicated that the physiological lactate concentration in blood or healthy tissues is approximately 1.5 – 3 mM ( 39 ), while the blood lactate levels in septic patients can reach over 20 mM ( 40 ). Remarkably, lactate levels can rise to 40 mM at the inflamed tissues ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study prognostic accuracy of serum lactate level, the SOFA score and qSOFA score for mortality among adults with sepsis conducted by Zhiqiang Liu, Zibo et al, documented that higher the lactate level poorer the outcome interms of mortality in sepsis patients. 16 Serum Lactate level is considered as a key tool in assessing the metabolic acidosis, hypoxia at tissue level which is mediated by shock either it can be septic shock or hypovolemic or cardiogenic shock. Increase in lactate levels is associated with multi-organ dysfunction and predicts the outcome in terms of length of hospital stay and mortality.…”
Section: %mentioning
confidence: 99%
“…Lower lactate levels with greater lactate clearance have consistently been associated with improved outcomes and lower mortality ( 19 21 ). In fact, a recent study by Liu et al ( 22 ) found lactate to be an independent predictor for mortality in septic patients. This has been substantiated by our study’s results, which demonstrated that higher mortality was not due to the vasopressor combination itself but rather due to the higher admission lactate level which was independently associated to the norepinephrine-vasopressin group.…”
Section: Discussionmentioning
confidence: 99%